Vietnam infantry tactics - Rottman, Gordon L. (Elite, 2011)
Reveals the evolving US, Viet Cong and NVA tactics at battalion level and below throughout the Vietnam War. Beginning with a description of the terrain, climate and the unique nature of operations, the author explains how unit organisation was broken down by combatant forces and the impact this had on the kind of tactics they employed.